Faktor-Faktor yang Mempengaruhi Kinerja Keuangan Usaha Koperasi (SHU) di Koperasi Unit Desa (KUD) Harapan Maju Desa Petaling Jaya Kecamatan Batang Cenaku Kabupaten Indragiri Hulu - R Marwan Indra Saputra; Aris Triyono (Universitas Batanghari, 2020)
This research is at the Village Cooperative Unit (KUD) Harapan Maju Petaling Jaya Village, Batang Cenaku District, Indragiri Hulu. This research used quantitative research, where the results of the analysis are presented in the form of figures which are then explained and interpreted in a description. The data used by the author in this study is secondary data and the research method used is descriptive method. From the results of the research it shows that: Own capital has no effect and is insignificant, the volume of business has a significant effect, assets have no effect and are significant for the acquisition of Remaining Operations (SHU), own capital, business volume and assets together affect the acquisition Remaining Operating Results (SHU) and there are other variables that affect the acquisition of Remaining Operations (SHU). Which is not examined in this study.